The impacts of family physician plan and health transformation plan on hospitalization rates in Iran: an interrupted time series - Samad Rouhani; Reza Esmaeili; Jamshid Yazdani Charati; Masoud Khandehroo (BMC, 2021)
Abstract Background Low and middle income countries has recently implemented various reforms toward Universal Health Coverage (UHC). This study aims to assess the impact of Family Physician Plan (FPP) and Health Transformation Plan (HTP) on hospitalization rate in Iran. Methods We conducted an Interrupted Time Series (ITS) design. The data was monthly hospitalization of Mazandaran province over a period of 7 years. Segmented regression analysis was applied in R version 3.6.1. Results A decreasing trend by − 0.056 for every month was found after implementation of Family Physician Plan, but this was not significant. Significant level change was appeared at the beginning of Health Transformation Plan and average of hospitalization rate increased by 1.04 (P < 0.001). Also hospitalization trend increased significantly nearly 0.09 every month in period after Health Transformation Plan (P < 0.001). Conclusions Family physician created a decreasing trend for hospitalization in urban area of Mazandaran province in Iran. HTP with lower user fee in governmental public hospitals and clinics as well as fee-for-service mechanisms, stimulated both level and trend changes in hospital admissions. Some integrated health policy is required to optimize the implementation of diverse simultaneous reforms in low and middle-income countries.